Effect of Rhythmic Cold Influence on the Activity of Some Enzymes in Aged Rats with Stimulated Hypertension - Samokhina, L. M. (Problems of Cryobiology and Cryomedicine, 2003)
The participation mechanisms of specific enzymes of angiotensin II (AII) formation such as chymase, tonin and elastase in the formation of an organism’s response to rhythmic cold influence (RCI) were investigated in aged rats under normal conditions and at the simulated hypertension (SH). It was revealed, that RCI occurred to be the stimulator for an aged organism, eliminated the consequences of ageing, by promoting the activation of such enzymes as tonin, elastase in healthy animals, chymase and tonin in rats with SH, as well as it prevented the elastase participation in the organ damage processes, caused by pathology development.